The cognitive processing of tone sandhi in different information structural status during dialogue comprehension. Issue 10 (26th November 2022) - Zheng, Zilong; Chien, Yu-Fu; Wang, Wenjing; Zhang, Zhenghua; Li, Weijun
ABSTRACT: Mandarin tone 3 (T3) sandhi is a phonological alternation where a T3 changes to a rising tone when followed by another T3. The present event-related potential (ERP) study examined how sandhi words are processed during dialogue comprehension. Following different wh-questions, the answers embedded a sandhi word in which the first syllable was either pronounced as post-sandhi T3, pre-sandhi T3, or mispronounced T4 at the focus or background position. The results showed that the naturalness rating decreased as the amplitude of a late positivity (LPC) increased in the order of post-sandhi, pre-sandhi, and mispronunciation conditions, reflecting a reanalysis process after encountering the unexpected tone. At the background (vs. focus) position, the effect was more posterior for the mispronunciation condition, and disappeared for the pre-sandhi condition. Our data suggest that the processing of sandhi words is not only influenced by their tonal realisation, but also moderated by their information structural status.